Effect of calcium carbonate replacement on workability and mechanical strength of portland cement concrete - Ali, Maisarah; Abdullah, Muhd Sufian; Saad, Siti Asmahani (2014)
Abstract. The continued growth of the world construction sectors has resulted in high demand for concrete materials. The innovation of using filler as a replacement for cement is becoming a trend in order to reduce the cement consumption and provide benefit in various ways. Hence forth, 10% of cement was replaced by the calcium carbonate (CaCO3) in this study. CaCO3 is a natural material, which has a finer particles size as compared to the cement particles. This improves particle packing of concrete and give spacer effect. The concrete with CaCO3 replacement possess a higher slump, which increased the workability. The specimens were prepared in 150mm x 150mm x 150mm mould. At 28 days, the water absorbed by hardened concrete was lower for CaCO3 as microscopy analysis indicates very low porosity in CaCO3 concrete. Mechanical properties tests were conducted in 3, 7 and 28 days. The CaCO3 helps to increase the early strength, due to the accelerator effect and high rate of hydration which hardens the concrete quicker. At matured age, the concrete with the CaCO3 addition exhibits lower strength as compared with concrete without CaCO3, but still within the target strength. Keywords: Calcium carbonate, ordinary Portland cement, particle packing, concrete workability and strength